A Critical Review on Smartphone Based Determinations of Drugs - Shrivastava, Alankar (Current Pharmaceutical Analysis, 2023)
Cell phones are like a notepad PC with their own working framework, processor, interior memory, and top-notch camera focal points. Cell phones are more open and less expensive than versatile analytical devices. The quantity of cell phone users overall outperformed 2 billion in 2016 and it addresses more than a fourth of the worldwide population. There have been numerous new articles on the utilization of cell phones as versatile detectors, bioanalytical equipment, and instrument interfaces. The utilization of cell phones has opened doors for prognostic, diagnostic, detection, observing, quantification, control, or making versatile applications, since it can be very well utilized to run routine tests. Moreover it does not require a trained personnel and it is convenient and considered a minimal-expense gadget. The development of analytical methods is crucial in drug development. Improvement of existing and execution of new methodologies are essential for the present-day analytical chemistry of drugs. Recently published studies focussed on some of the applications of smartphone-based analytical methodologies in the last few years for the determination of drugs in different matrices. The aim of the presented review was to enhance the visibility of one of the fast and novel applications of smartphone technology. This will help scientists and researchers to understand the recent developments and explore new possibilities in this field.
Keywords: spectrophotometry